Empire and its double: The many pavilions of the Islamic State - Staal , Jonas (Re-visiones, 2024)
On March 7, 2015, the day e-flux journal no. 63 is published, I receive a text message from my colleague Younes Bouadi. The e-flux website is hacked, it reads. Upon opening the site, an Islamic chant fills my room. Reprinted and translated with permission from e-flux journal #65 SUPERCOMMUNITY, May-August 2015, July 12, 2015 [07.12.15] / 09:05:09 EDT